Effect of periodontal therapy on the subgingival microbiota over a 2‐year monitoring period. I. Overall effect and kinetics of change. (27th May 2013) - Socransky, Sigmund S.; Haffajee, Anne D.; Teles, Ricardo; Wennstrom, Jan L.; Lindhe, Jan; Bogren, Anna; Hasturk, Hatice; van, Thomas; Wang, Xiaoshan; Goodson, Jo Max
Abstract Aim To examine the 2‐year post‐therapy kinetics of change in the composition of subgingival biofilms. Material and Methods In this study, 178 chronic periodontitis subjects were recruited and clinically monitored at baseline, 3, 6, 12, 18 and 24 months after therapy. All subjects received scaling and root planing and 156 one or more of periodontal surgery, systemically administered amoxicillin + metronidazole or local tetracycline at pockets ≥5 mm. Subgingival biofilm samples taken from each subject at each time point were analysed for their content of 40 bacterial species using checkerboard DNA–DNA hybridization. The significance of changes in median species counts over time was sought using the Wilcoxon or Friedman tests and adjusted for multiple comparisons. Results Mean counts were significantly reduced from baseline to 2 years for 30 of the 40 taxa. Marked reductions were observed for periodontal pathogens including Tannerella forsythia, Treponema denticola and Eubacterium nodatum. The kinetics of change differed from species to species. When data were subset according to baseline PD, patterns of change in the microbial profiles were generally similar. Conclusion Periodontal therapy leads to a rapid reduction in periodontal pathogens, followed by a slower reduction in other taxa that can be sustained for at least 2 years.